Dynamic Analysis of the Propulsion Process of Tunnel Boring Machines - Liao, Xiangping; Zhao, Ying; Kang, Shaopeng; Liu, Kailei; Zhu, Xinyang; Sun, Langxin (Manufacturing Technology Journal, 2024)
In response to the need for trajectory correction during the excavation of curved tunnels by tunnel boring machines(TBM), as well as the impact of interference forces generated by the propulsion sys-tem on the design and service life of key components, as well as the low propulsion efficiency of TBM, a dynamic model of the propulsion mechanism during the excavation process is established, and the variation law of the angle between the key components of the thrust hydraulic cylinder and the gripper shoe hydraulic cylinder under the propulsion force of the hydraulic cylinder (1500KN) and three steer-ing angles of 0.5 °, 1 °, and 2 °, as well as the relationship between the gripper shoe hydraulic cyl-inder tightening force and horizontal propulsion force, has been studied. Research has shown that under the rated hydraulic cylinder propulsion force, during the process of increasing the swing angle of the main beam, the left angle and the tightening force on the left gripper shoe are less than the straight-line working condition, while the right side is greater than the straight-line working condition. However, during the forward excavation process after turning left, the X-direction propulsion force provided by the left thrust cylinder is greater than the X-direction propulsion force of the horizontal excavation, and the force on the left support shoe is less than the tightening force under the horizontal working condition, while the opposite is true for the right side. The research results have important theoretical significance for studying the optimal matching relationship between the mechanical model and excavation parameters of TBM during the propulsion process, as well as further improving the excavation efficiency and stability of TBM.
Keywords: TBM; Propulsion process; Thrust mechanism; Propulsion simulation